Avaliação da resistência à corrosão do aço-manganês austenítico em meio ácido, básico e salino, utilizando as técnicas de polarização linear potenciodinâmica e espectroscopia de impedância eletroquímica - Moreira, Henrique Fernandes (Universidade Federal Rural do Semi-Árido, 2016)
Corrosion is a spontaneous process that metals and alloys are susceptible to particular means, so that inspection and monitoring are needed for the use thereof to prevent direct and indirect losses. Knowing what material to use in each medium helps reduce repair costs, environmental damage and accidents (personal and property safety). This paper evaluated the corrosion resistance of the steel-manganese austenitic in acidic, basic and salt, applying the techniques of linear polarization potentiodynamic and electrochemical impedance spectroscopy. In order to determine their potential for future applications of the material in the industry and application of theoretical knowledge to the analysis and interpretation of experimental data.
Keywords: Corrosão; Manganês; Aço; Corrosion; Manganese; Steel; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA